Does substrate influence germination of Cinchona pubescens Vahl. (Rubiaceae)?; ¿Tiene influencia el sustrato sobre la germinación de Cinchona pubescens Vahl. (Rubiaceae)? - Fernandez-Zarate, Franklin Hitler (2022)
Cinchona pubescens is an emblematic species of Peru, as it was used as the only effective treatment against malaria for three centuries. This species is threatened by various anthropogenic activities and its propagation depends on the dispersal of seeds whose germination power is low, therefore, it is necessary to conserve and propagate it. The objective of the study was to evaluate the effect of substrate on the germination of C. pubescens. A completely randomized design was applied with five treatments according to the type of substrate T1 (25% forest soil+75% sand), T2 (50% forest soil+50% sand), T3 (75% forest soil+25% sand), T4 (100% forest soil) and T5 (100% sand), the forest soil was extracted from areas where C. pubescens is naturally present. Three replicates and 100 seeds per replicate were used in the treatments. Germination of C. pubescens started 12 days after sowing until day 42. T4 had a better effect on the index (14.23±0.41), time (24.18±0.69) and germination percentage (88.3±2.88%); followed by treatments T3 and T2. While T5 was the treatment with the least effect on C. pubescens germination. The study indicated that the type of substrate used significantly influences the germination of C. pubescens seeds, so it is suggested to use substrate from natural forest without combination to achieve high germination rates and propagation of this species.